On Groves mechanisms for costly inclusion - Andrew MacKenzie; Christian Trudeau (Theoretical Economics, 2023)
We investigate Groves mechanisms for economies where (i) a social outcome specifies a group of winning agents, and (ii) a cost function associates each group with a monetary cost. In particular, we characterize both (i) the class of cost functions for which there are Groves mechanisms such that the agents cover the costs through voluntary payments, and (ii) the class of cost functions for which there are envy-free Groves mechanisms. It follows directly from our results that whenever production efficient and envy-free allocations can be implemented in dominant strategies, this can moreover be done while funding production through voluntary payments.
Keywords: D82; D47; D24; D44; H41; D61; D63; 330; Costly inclusion; free-rider problem; Groves mechanism; labor markets; pivot mechanism; Vickrey auction